PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GIVING QUESTION AND GETTING ANSWER TERHADAP HASIL BELAJAR IPS SISWA SMP N 25 PADANG - Bunda, Pitriana Permata; Zafri, Zafri; Husnita, Liza (Pendidikan Sejarah, 2014)
Learning processes is student should get be active to arrange and constructing also there is collaborative which student can work together to understand a study which finally will impact to result study of student are low because learning method character one direction to delivery informations until students are not accustomed to facts interpretation. One of ways to improve facts interpretation in history learning is giving queation and getting anwer model. The puspose of this research is to know the effect in applying model to result of study students hystory at SMP Negeri 25 Padang. The kind of this research is quantitative. The data which is gotten through experiment at student grade VII SMP Negeri 25 Padang. The choosing sampel in this research based on group randomly with a assumption that every groups have sames ability and habit in study history subject. Experiment class is class VII.4 and control class is class VII.5. Based on the data which is processed, result of study giving fact interpretation that score achievement history of experiment class higher than control class. This case can be seen at posttest value of experiment class is 8,17 and posttest value of control class is 6,52. So that the improving result of study to history facts interpretation of experiment class higher than control class. It can be concluded that applying learning model of giving question and getting answer give influence to result study of student. This method can be used as an alternative way to apply it in the class by teachers to improve the interest and result study of student.